2021
DOI: 10.1097/01.npr.0000753832.85114.65
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors

Abstract: Sodium-glucose cotransporter-2 (SGLT2) inhibitors can decrease risk for heart failure in patients with type 2 diabetes and can decrease risk of major cardiovascular events in patients with heart failure (HF)and diabetes. Specifi c SGLT2 inhibitors can also decrease major cardiovascular events in patients with HF only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…Improving heart failure symptoms work by targeting both the preload and the after-load; the former will be regulated by the decrease in plasma volume, whereas the latter is decreased by lower blood pressure, ultimately leading to better cardiac flow. On the other hand, SGLT2i work by reducing arterial stiffness via relaxation of the smooth muscle cells 32 . Patients hospitalized for acute heart failure were usually excluded from clinical trials on SGLT2i.…”
Section: Sodium-glucose Cotransporter 2 Inhibitors In Acute Heart Fai...mentioning
confidence: 99%
See 1 more Smart Citation
“…Improving heart failure symptoms work by targeting both the preload and the after-load; the former will be regulated by the decrease in plasma volume, whereas the latter is decreased by lower blood pressure, ultimately leading to better cardiac flow. On the other hand, SGLT2i work by reducing arterial stiffness via relaxation of the smooth muscle cells 32 . Patients hospitalized for acute heart failure were usually excluded from clinical trials on SGLT2i.…”
Section: Sodium-glucose Cotransporter 2 Inhibitors In Acute Heart Fai...mentioning
confidence: 99%
“…On the other hand, SGLT2i work by reducing arterial stiffness via relaxation of the smooth muscle cells. 32 Patients hospitalized for acute heart failure were usually excluded from clinical trials on SGLT2i.…”
Section: Action Of Sodium-glucose Cotransporter 2 Inhibitors In Heart...mentioning
confidence: 99%
“…11 The use of SGLT2 inhibitors can be expensive and nurses can provide support by referring patients to the drug manufacturer for financial and copay assistance. 12 Lastly, the nurse should review nonpharmacologic treatment such as a low-sodium diet, exercise as tolerated, and if appropriate, cardiac rehabilitation.…”
Section: Implications For Nursing Carementioning
confidence: 99%
“…Additionally, patients should report any rashes, changes in vaginal or penile discharge, anal itching, pain, swelling or discoloration of the genitals, as this could indicate that the patient is experiencing a fungal infection or is developing Fournier gangrene, a necrotizing fasciitis in the genital area 11. The use of SGLT2 inhibitors can be expensive and nurses can provide support by referring patients to the drug manufacturer for financial and copay assistance 12. Lastly, the nurse should review nonpharmacologic treatment such as a low-sodium diet, exercise as tolerated, and if appropriate, cardiac rehabilitation.…”
Section: Implications For Nursing Carementioning
confidence: 99%
“…Furthermore, studies have shown that in patients with heart failure with reduced and preserved ejection fraction, regardless of type 2 diabetes, SGLT2 inhibitors can minimize disease progression, hospitalizations, and deaths from all causes. 7,8 Nonetheless, the mechanism of SGLT2 inhibitors in cardiovascular protection is complex and warrants further study. Outside of phase III studies, there is limited information concerning the characterization of each agent and the situations where each one would stand out as the better option, especially in Latin America.…”
Section: Introductionmentioning
confidence: 99%